Low pass conditioning filter in the dq synchronous frame for DFIG systems based on the power transfer matrix - Abu-Hajar, A.; Al-Durra, A.; Muyeen, S.M. (2015)
In this paper, a low pass conditioning filter in the dq synchronous reference frame that removes noise and oscillation from the control signals of the DFIG controllers is proposed. The cutoff frequency of the conditioning filter is based on the power transfer matrix of the DFIG system. The power transfer matrix elegantly linearizes the DFIG's state space matrices using small signal approximation. We have investigated the effect of the different parameters on the bandwidth of partial transfer functions of the DFIG system. We were able to determine the bandwidth of the DFIG system by evaluating the dominating poles of the system. This is achieved by solving for the roots of the characteristic equation of the linearized state matrices of the power transfer matrix model. The low pass conditioning filter was used to remove additive Gaussian noise from the control signals. The proposed filter was simulated using Simulink/PowerSysTool, and the simulation showed that additive Gaussian noise was removed while the DFIG operated near its optimal power extraction point